Inhibitory effects of Chikusetsusaponin IVa on lipopolysaccharide-induced pro-inflammatory responses in THP-1 cells. (September 2015) - Wang, H; Qi, J; Li, L; Wu, T; Wang, Y; Wang, X; Ning, Q
This study investigated anti-inflammatory effects and possible mechanisms of Chikusetsusaponin IVa (Chi IVa), one of the main bioactive components in saponins from Panacis japonica (SPJ), which is used in traditional Tujia and Hmong Chinese medicine. To this end, changes in the inflammatory profiles of lipopolysacchride (LPS)-stimulated phrobol 12-myristate 13-acetate(PMA)-differented THP-1 macrophages were evaluated following Chi IVa treatment. The results showed that Chi IVa markedly decreased the expression of inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), interleukin-1 beta (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) at both the mRNA and protein level, which proved to be dose-dependent. Further studies revealed that Chi IVa strongly suppressed NF-κB activation and downregulated the phosphorylation of ERK, p38, and JNK. Our present study demonstrates that Chi IVa suppresses the production of iNOS, COX-2, IL-1β, IL-6, and TNF-α in LPS-stimulated THP-1 cells likely by inhibiting NF-κB activation and ERK, JNK, and p38 signal pathway phosphorylation.